Growth, Nutrition and Economy : Proceedings of the 27th Aschauer Soiree, held at Krobielowice, Poland, November 16th 2019 - Hermanussen, Michael (2021)
Twenty-three scientists met at Krobielowice, Poland to discuss the role of growth, nutrition and economy on body size. Contrasting prevailing concepts, re-analyses of studies in Indonesian and Guatemalan school children with high prevalence of stunting failed to provide evidence for an association between nutritional status and body height. Direct effects of parental education on growth that were not transmitted via nutrition were shown in Indian datasets using network analysis and novel statistical methods (St. Nicolas House Analysis) that translate correlation matrices into network graphs. Data on Polish children suggest significant impact of socioeconomic sensitivity on child growth, with no effect of maternal money satisfaction. Height and maturation tempo affect the position of a child among its peers. Correlations also exist between mood disorders and height. Secular changes in height and weight varied across decades independent of population size. Historic and recent Russian data showed that height of persons whose fathers performed manual work were on average four cm shorter than persons whose fathers were high-degree specialists. Body height, menarcheal age, and body proportions are sensitive to socioeconomic variables. Additional topics included delayed motherhood and its associations with newborn size; geographic and socioeconomic indicators related to low birth weight, prematurity and stillbirth rate; data on anthropometric history of Brazil, 1850-1950; the impact of central nervous system stimulants on the growth of children with attention-deficit/hyperactivity disorder; and pituitary development and growth hormone secretion. Final discussions debated on reverse causality interfering between social position, and adolescent growth and developmental tempo.